Added value of cardiac computed tomography for evaluation of mechanical aortic valve: Emphasis on evaluation of pannus with surgical findings as standard reference. (1st July 2016) - Suh, Young Joo; Lee, Sak; Im, Dong Jin; Chang, Suyon; Hong, Yoo Jin; Lee, Hye-Jeong; Hur, Jin; Choi, Byoung Wook; Chang, Byung-Chul; Shim, Chi Young; Hong, Geu-Ru; Kim, Young Jin
Abstract: Background: The added value of cardiac computed tomography (CT) with transesophageal echocardiography (TEE) for evaluating mechanical aortic valve (AV) dysfunction has not yet been investigated. The purposes of this study were to investigate the added value of cardiac CT for evaluation of mechanical AVs and diagnoses of pannus compared to TEE, with surgical findings of redo-aortic valve replacement (AVR) used as a standard reference. Methods: 25 patients who underwent redo-AVR due to mechanical AV dysfunction and cardiac CT before redo-AVR were included. The presence of pannus, encroachment ratio by pannus, and limitation of motion (LOM) were evaluated on CT. The diagnostic performance of pannus detection was compared using TEE, CT, and CT + TEE, with surgical findings as a standard reference. The added value of CT for diagnosing the cause of mechanical AV dysfunction was assessed compared to TTE + TEE. Results: In two patients, CT analysis was not feasible due to severe metallic artifacts. On CT, pannus and LOM were found in 100% (23/23) and 60.9% (14/23). TEE identified pannus in 48.0% of patients (12/25). CT, TEE, and CT + TEE correctly identified pannus with sensitivity of 92.0%, 48.0%, and 92.0%, respectively (P = 0.002 for CT vs. TEE). In 11 of 13 cases (84.6%) with inconclusive or negative TEE results for pannus, CT detected the pannus. Among 13 inconclusive cases of TTE + TEE for the cause of mechanical AV dysfunction, CT suggested 6 prosthetic valve obstruction (PVO) by pannus, 4 low-flow low-gradient PVO, and one LOM without significant PVO. Conclusions: Cardiac CT showed added diagnostic value with TEE in the detection of pannus as the cause of mechanical AV dysfunction.